PEMETAAN CEPAT (RAPID MAPPING) PAJAK BUMI DAN BANGUNAN PEDESAAN PERKOTAAN (PBB-P2) TAHUN 2023 (Studi Kasus Pada Jorong Cupak Nagari Pakan Sinayan Kecamatan Banuhampu Kabupaten Agam) - Ramadhan, Hafizh Edda; wa, erna (JURNAL BUANA, 2026)
Regional original income (PAD) is a type of regional income managed by regional governments, and one of them is Urban and Rural Land and Building Tax (PBB-P2). The data used in the existing PBB-P2 data collection is not relevant to current field conditions and it is important to update and test the data according to the technical guidelines of the Directorate General of Taxes number se-19/PJ.6/2003. This research aims to: 1) remap the tax area in Jorong Cupak and 2) test the mapping results using a wide difference tolerance test with a wide difference error limit of 10%. This research will use a type of geographic survey research with quantitative descriptive research methods which will focus on rapid mapping by utilizing community participation in interpreting Quickbird images for mapping and carrying out tolerance tests for the broad quality of tax objects for all tax objects resulting from mapping with the system. total sampling test. This research resulted in updated data reaching 149 tax objects in the Jorong Cupak sub and 51 tax objects in the Jorong Sijawijawi sub, with the Jorong Cupak sub having 52 new data or 35% and the Jorong Sijawijawi sub having 44 new data or 86%. And by carrying out a wide difference tolerance test, 184 data met the wide quality tolerance test or 91.54% and 17 data did not meet the wide quality tolerance test or 8%.